Projection of “Dibya Upadesh” of Prithvi Narayan Shah: Lessons for Small State Diplomacy in Contemporary World Affairs - Jayshwal, Vijya Prasad; Shah, Seema Kumari (KMC Research Journal, 2022)
The narratives of small state diplomacy are not a recent phenomenon in international relations and world affairs. The projection of state like Nepal in classical era as ’sandwich’ between two giant economy was classical reflection of it. Nepal has always observed and followed the balanced foreign policy with neighbours and also with external entities and it was a clear idea in Dibya Upadesh of late King Prithvi Narayan Shah which is still relevant and contextual. The small state diplomacy has been a subject of contestation and a discourse to locate the role of small state in international relations and foreign affairs. The collective growth of small states seems challenging in contemporary affairs. Nepal is projected as a small state qualifying all criteria to be considered or defined as small state. The diplomatic move played in past was literally an articulated step for presenting power of small states in world affairs. The reflection in Upadesh is also an ancient depiction of it. This paper has analysed the projection of Nepal as small state and its relevancy in contemporary world affairs.